A Novel Approach for Reconstructing Slip Histories for Bedrock Fault Scarps Using Rock Surface Luminescence Dating. Issue 16 (16th August 2022) - Luo, Ming; Chen, Jie; Owen, Lewis A.; Qin, Jintang; Yin, Jinhui; Yang, Huili; Liu, Jinfeng; Gong, Zhijun; Luo, Jiahong
Abstract: A newly developing method, optically stimulated luminescence (OSL)‐depth profiles (DPs), provides a novel means of reconstructing and quantifying fault slip on timescales of 10 1−4  years. A targeted bedrock fault scarp along Langshan in north China, used as proof of concept, is divided into four sections based on four groups of OSL‐DPs at different heights up the bedrock fault scarp. These have seismic displacements of 170, 80, 130, and 140 cm, and without considering the erosion rate, the exposure ages at the four displacements are 6–35 a, 19–84 a, 0.5–0.9 ka, and 2–5 ka, respectively. The ages are overall in chronological order, while the actual ages are likely underestimated due to erosion. After assuming erosion amounts according to the weathering characteristics, the calculated ages are mostly consistent with paleoseismic trenching studies. In addition, the method may identify a seismic event that previous studies did not identify. Plain Language Summary: Bedrock fault scarps are among the best natural archives to help constrain and date fault slip. Bedrock fault scarps record many seismic events but lack suitable dating methods on timescales of 10 1−4  years to define the timing of fault movement. Optically stimulated luminescence (OSL) surface exposure dating provides a novel means of differentiating seismic displacements, quantifying ages, and bedrock erosion rates for bedrock fault scarps. We apply this method to bedrock fault scarps of the Langshan piedmont fault in north China as a proof of concept. Adopting the k ‐means clustering method to OSL‐depth profiles (DPs), the fault scarp below 6 m records four seismic event with fault displacements of 170, 80, 130, and 140 cm. The exposure ages obtained by OSL‐DPs methods are somewhat underestimates if erosion rates are not considered. However, the ages are better corrected after assuming the amount of erosion based on weathering characteristics evident in the field. Our study shows that this method is a valuable supplement to paleoseismic trenching and bedrock fault scarps dating methods, and it helps extend the understanding and usefulness of bedrock fault scarps. Key Points: We perform one of the first studies attempting to use optically stimulated luminescence‐depth profiles as a quantitative proxy of bedrock fault scarps slip history Results show that the method can quantify seismic displacements, age, and erosion rates for bedrock faults on timescales of 10 1−4  years We define the uncertainties on the depth of half saturation (DHS) using the horizontal width of the 95% confidence intervals at DHS